Ontogenetic development of electrocorticogram in the rat - Mares, P; Zouhar, A; Brozek, G (Activitas nervosa superior, 1979)
Spontaneous electrocorticogram (ECoG) was recorded in frontal (sensorimotor) temporal (auditory) and occipital (visual) cortical regions of 86 male rats (immobilized with d-tubocurarine) aged from 3 days to adulthood. Activity which could be classified as ECoG was for the first time recorded in 5-day-old rats; it was formed by groups of slow waves with unstable frequency intermingled with periods of isoelectric line. Discontinuous ECoG activity was regularly registered even in 10-day-old rats, exceptionally in 12-day-old rats. During further maturation of the continuous ECoG an increase in frequency and an establishment of a basic rhythmic activity synchronous over both hemispheres took place, so that 25- and 30-day-old rats did not differ from the adult ones. Autocorrelagrams and power frequency spectra demonstrated a broad frequency range of the basic rhythm as well as delay in the development of occipital cortical areas in comparison to frontal areas.
Keywords: Electroencephalography; Aging; Male; sluchové korové centrum; Somatosensory Cortex; elektroencefalografie; mozková kůra; mužské pohlaví; motorické korové centrum; krysa rodu Rattus; Animals; Motor Cortex; zrakové korové centrum; Auditory Cortex; zvířata; Rats; stárnutí; Visual Cortex; somatosenzorické korové centrum; Cerebral Cortex